Teacher Perception Towards the Implementation of Independent Learning Curriculum - Wildani, Mohammad Shaleh; Fauzi, Ahmad; Solihin, Mohamad (Journal of Educational Management Research, 2025)
This study examines teachers' perceptions of the implementation of the Independent Curriculum using a library research approach. The scope of the study includes teachers' understanding, readiness, and challenges faced in implementing the curriculum. The purpose of this study is to analyze how teachers interpret the Independent Curriculum and the factors that influence their perceptions. Data were collected through literature studies from various sources such as journals, books, and relevant scientific articles. The results of the study show that most teachers have a positive perception of the flexibility and freedom of learning offered by the Independent Curriculum. However, there are also obstacles such as limited understanding, lack of training, and the availability of adequate facilities and infrastructure. The conclusion of this study states that the success of the implementation of the Independent Curriculum is greatly influenced by teacher readiness, policy support, and adequate supporting facilities.